Open Source Web Development with LAMP Using Linux, Apache, MySQL, Perl, and PHP - Lee, James; Ware, Brent (Addison-Wesley Professional, 2002)
Open Source technologies are providing contemporary developers with a range of cost-effective and robust alternatives to commercial software for building dynamic, data-driven Web applications. This practical guide presents a comprehensive survey of LAMP (Linux, Apache, MySQL, Perl, and PHP), and it shows how these solutions can be implemented efficiently and securely while improving reliability and dramatically cutting costs. Open Source Web Development with LAMP focuses on the most important core material necessary so that developers can "hit the ground running" and begin building applications right away. This book presents a balanced overview of LAMP technologies and allows the reader to decide which tool may be appropriate for the particular task at hand. After a general overview of Open Source technologies, the book presents an overview of the Web before moving on to cover structural, static, dynamic, and embedded technologies. The coverage here provides a description of the strengths and weaknesses of each Open Source technology and also acts as a reference guide for each application. Topics covered include: A comprehensive survey of Open Source technologies Static and dynamic data and embedded HTML on the Web Linux and Unix distributions, installations, and commands Apache Web Server, Perl, and MySQL Web site META language (WML) Common gateway interface (CGI) and mod_perl Server Side Includes (SSI), Embperl, and Mason PHP syntax and functions In addition to the discussions in the book, a companion Web site--www.opensourcewebbook.com--contains supplemental information, including tools, source code, helpful links to additional resources, and errata as needed. Complete in coverage and practical in presentation, Open Source Web Development with LAMP spotlights the tools and technologies today's developers need to create workable, dynamic, and secure Web sites using Open Source technologies. 020177061XB11072002.
Keywords: Computer software -- Development; Computer software; Development